(untitled) (Journal of Engineering Science, 2025)
Falls are one of the major causes of unintentional injury, deaths in the world and pose a critical threat to occupational safety, particularly in the construction industry. Worldwide, falls account for 684,000 lives per year with construction industry being responsible for 38% of the cases. According to the latest statistics, in Bangladesh alone, 185 construction worker deaths were recorded, of which 70 solely resulted from falling. Therefore, it is imperative to address the issue. This study investigates the root causes of fall hazards at construction sites in Bangladesh. The data collection was carried out through a questionnaire and physical survey of ten construction sites within Dhaka city. 20 items of questions divided into 7 Groups of Factors were developed through an extensive literature review. The data from the questionnaire survey were then analyzed through SPSS 27 statistical software to measure descriptive statistics; reliability and validity were measured by Cronbach’s α and Spearman-Brown coefficient. Later on, from the physical survey risk metrics was generated. Finally, this study suggests regular workplace inspections, improved enforcement of OSH regulations, safety awareness campaigns, and development/integration of site-specific training programs, along with technological innovations such as drones and wearable sensors to curb the fall hazards. Synergizing these initiatives with Sustainable Development Goals 3 (Good Health and Well-Being) and 8 (Decent Work and Economic Growth) will build safer workplaces, reducing deaths and enabling the construction industry return on economic sustainability for Bangladesh. Journal of Engineering Science 15(2), 2024, 69-78